Representações sociais e meio ambiente: participação de um grupo de mulheres no planejamento de uma intervenção de educação ambiental popular urbana em Manaus, Amazonas - Storey, Christine (Universidade Federal de São Carlos, 2003)
The central argument of this thesis is to promote the importance of observing peoples’ understanding of their environment in order to develop a popular environmental education programme with rather than for them, one that fosters participatory solidarity. As such, ecofeminismo and the theory of social representations have been explored as possible theories and practices to assist environmental educators in this task. This has been approached in three articles the first of which is about the theory and practice of ecofeminismo as possible directions for environmental education. As ecofeminism offers elements to understand the complex power interrelations and the increasing environmental inequalities that exist in contemporary society. Furthermore it proposes the deconstruction of the dualities that permeate our society and feed such inequalities. In the same direction, in the second article we present a research paper that applied the theory of social representations to assist in interpreting of the lifestyles, perceived needs and environmental activities, with a group of 10 urban women from Manaus, Amazonas, Brazil. The interpretation of the environmental social representations revealed some of the women's environmental practices and understanding, and that religion, situation, media, identity and cultural heritage are five mediators that influence the production of such representations. The results offered important information on the participants' theoretical frameworks; the final task was to verify if such data would assist in planning a popular environmental education intervention. The third article is a report on such a verification, which occurred during a workshop with a larger number of residents from the same neighbourhood. In which three themes detected in the research results were presented to the participants for them to choose one for the educational intervention. Handicrafts were selected and the intervention is at the present moment in full activity. This confirms, that although the theory of social representations cannot solve all the difficulties that environmental education faces in an unsustainable society; it can, assist in understanding people better and from this promote the construction of solidarity. The expected outcome is that the three papers bring elements to be debated within environmental education. Also that the group the women formed will flourish permitting them to grow together.
Keywords: Meio ambiente; Educação ambiental popular; Representação social; Ecofeminismo; Manaus (AM); Mulheres; Environmental education; Ecofeminismo; Social representations; Educational intervention; Women; Manaus-Amazonas; CIENCIAS BIOLOGICAS::ECOLOGIA